The Epigenetic Landscape of Promoter Genome-wide Analysis in Breast Cancer - KARSLI, SEHER (NATURE PUBLISHING GROUP, 2017)
Breast cancer is a heterogeneous disease due to its clinico-pathological features and response to therapy. The classification of breast tumors based on their hormone receptor status and pathologic features. Post-translational histone modifications come into prominence for regulation of gene expression in cancer pathogenesis. Here, we analyzed dysregulation of H3K9ac and H3K27me3-enriched subtype-specific genes using ChIP-on-chip assay in breast cancer tumors and matched normal tissue samples. Breast cancer tumors were classified according to St Gallen Consensus 2013. Our results indicated that the promoter regions of genes modified by H3K9ac epi-mark are commonly associated with tumors with HER2-positive and TNBC subtype. H3K27me3-enriched genes were comprised of Luminal A and B1 subtypes. We constructed a network structure to elicit epigenetically regulated genes related with breast cancer progression. The central genes of the network (RUNX1, PAX3, GATA4 and DLX5) were subjected for epigenetically dysregulation in association with different breast cancer subtypes. Our study submits epigenetic mechanisms are crucial to elicit subtype-specific regulation in breast cancer and ChIP-on-chip assay provides a better understanding for breast tumorigenesis and new approaches for prevention and treatment.
Keywords: INTERNATIONAL EXPERT CONSENSUS; HISTONE MODIFICATIONS; PROGNOSTIC-FACTORS; PRIMARY THERAPY; SUBTYPES; CELLS; TRIMETHYLATION; ACETYLATION; ASSOCIATION; METHYLATION